T20 Brasil: Communiqué and implementation roadmaps - CEBRI Rethink Tank; Instituto de Pesquisa Economica Aplicada; Fundacao Alexandre De Gusmao (Centro Brasileiro de Relacoes Internacionais, 2024)
The world is experiencing a polycrisis as it slowly and unevenly recovers from the COVID-19 pandemic. This polycrisis is characterized by interconnected and cascading geopolitical, socioeconomic, and environmental risks and threats. The evermore tangible impacts of climate change and biodiversity loss are compounded by rising international and internal armed conflict, deepening economic inequalities and financial instability, with developing countries, particularly low-income ones, facing persistently high debt levels and shrinking fiscal space. The latter jeopardizes their capacity to increase investments that are necessary to catch up on lagging outcomes related to the Sustainable Development Goals (SDGs)